Interpretarea juridică: de la elemente juridice și politice la bun simț [Articol] - Aramă, Elena (Tipografia Artpoligraf, 2019)
Legal interpretation is a matter of major importance for the legal field, both theoretical and practical. Both the drafting authority and those implementing the law must take into account the values guiding the society in which lawmaking and enforcement processes take place. Democratic constitutional regimes proclaim the principle of separation ofpowers, ie of the three powers: legislative, executive and judicial. This principle in its contemporary version means not the rigid separation, the isolation of each power, but also the cooperation between powers, resulting in such a balance of power, that thanks to the brakes and counterweights provided by the Constitution and laws each of the three powers cannot slip into abuse, and in the presence of these mechanisms the democratic regime of the state is strengthened. A truly democratic regime does not mean parliamentary absolutism, it is not just the ruling of the majority, especially since under the conditions of multiparty elections and the parliamentary majority can represent less than half of the electorateofastate.
Legal interpretation: from legal and political elements to common sense
Keywords: legal interpretation; democratic constitutional regimes; rule of law